O início da residência médica no hospital das clínicas da universidade federal de Minas Gerais - Nathayl Elisa Mucci (2011)
This work proposed to rescue the beginning of medical residence at Clinical Hospital of Federal University of Minas Gerais, through interviews and documental research, based on Oral History theories. A total of 23 interviews were conducted, with 21 professors and residents of the decades from 1950 to 1970 and 2 Clinical Hospital employees from the same decades. The documental research went beyond the history of Medical Residence getting to the history of all institutions involved in this process of teaching/training (Federal University of Minas Gerais, Medical School and Clinical Hospital) and to a short sketch of historical and social context. The result of the research was the organized record of this beginning, fulfilling the gap that existed before; and providing the basis for new reflections about the Medical Residence at Clinical Hospital of Federal University of Minas Gerais